Synthesis and biological evaluation of new N-substituted-N '-(3,5-di/1,3,5-trimethylpyrazole-4-yl)thiourea/urea derivatives - KAYMAKÇIOĞLU, BEDİA; ARICIOĞLU, FEYZA (ELSEVIER SCIENCE BV, 2005)
Several thiourea and urea derivatives were prepared by the reaction of 4-aminopyrazoles with substituted isothiocyanates or isocyanates. The novel compounds were tested anticonvulsant activity using by pentylenetetrazole-induced seizure (PTZ) and maximal electroshock seizure (MES) tests. Among the tested compounds, thiourea derivatives of 4b were afforded 90 and 100% protection in PTZ and MES tests at 50 mg/kg, respectively. Urea derivatives of 5a and 5b were afforded 82 and 100% protection both at 25 and 50 mg/kg. Also synthesized compounds were screened for antituberculosis activity against Mycobacterium tuberculosis H(37)Rv at 6.25 mu g/mL concentration but they were not found active at these concentration. In addition, some selected compounds were evaluated for in vitro anti-HIV activity and they were all negative. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: anticonvulsant activity; 3,5-dimethylpyrazole; thiourea; urea; ANTICONVULSANT ACTIVITY; THIOUREA; SEIZURE; ANALOGS; UREAS